Influence of pneumonia complications on the prognosis of patients with autopsy‐confirmed Alzheimer's disease, dementia with Lewy bodies, and vascular dementia. Issue 5 (29th October 2015) - Manabe, Toshie; Mizukami, Katsuyoshi; Akatsu, Hiroyasu; Teramoto, Shinji; Yamaoka, Kazue; Nakamura, Seiji; Ohkubo, Takayoshi; Kudo, Koichiro; Hizawa, Nobuyuki
Abstract: Background: Pneumonia is a major, complicated disease in patients with dementia. However, the influence of pneumonia on the prognosis of patients with varying types of dementia has not been fully evaluated. Methods: We retrospectively analyzed the data from medical and autopsy reports. All study patients had been hospitalized and underwent brain autopsy in a hospital in Toyohashi, Japan, between 2005 and 2014. The patients with subtypes of dementia, specifically Alzheimer's disease (AD), dementia with Lewy bodies (DLB), or vascular dementia (VaD), were neuropathologically diagnosed and examined. Pneumonia incidence, cause of death, and the clinical time‐course of dementia were compared among the dementia subtypes. The time to death from dementia onset (survival time) was compared by the Kaplan–Meier method among subtypes of dementia with or without pneumonia. Risk factors for survival time on all study patients were analyzed with the Cox proportional hazard model. Results: Of the 157 eligible patients, 63 (40.1%) had AD, 42 (26.8%) had DLB, and 52 (33.1%) had VaD. Pneumonia complication was observed with high incidence in each subtype of dementia, especially in DLB (90.5%). The median total duration from dementia onset to death was 8 years in AD and DLB, and 5 years in VaD. The VaD subtype had more male patients than AD or DLB ( P = 0.010), and age of death in this group was the youngest among the three groups ( P = 0.018). A significant difference was observed in the survival time by the Kaplan–Meier method among the three groups ( P < 0.001) and among the groups with pneumonia ( P = 0.002). The factors associated with shorter survival time were male gender, pneumonia complications, diabetes mellitus, age of dementia onset ≥ 75 years, and VaD. Conclusions: Pneumonia complications shortened the survival time of patients with AD, DLB, and VaD.